2016
DOI: 10.1111/jre.12367
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of E‐cadherin by Porphyromonas gingivalis‐lipopolysaccharide attenuates epithelial barrier function

Abstract: These results suggest that the decrease in E-cad caused by P. gingivalis-LPS leads to destruction of the epithelial barrier function in human gingival epithelial cells, and finally accelerates the inflammatory reaction under the barrier. Antioxidants, particularly vitamin E and l-ascorbic acid 2-phosphate magnesium salt, may restore the impaired function by scavenging ROS, which are related to the decrease in E-cad expression by P. gingivalis-LPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 27 publications
6
29
0
4
Order By: Relevance
“…This finding was in agreement with the results from previous studies which indicated downregulation of E‐cadherin expression in the inflamed periodontal tissue in vivo and in vitro, and this was mostly attributed to gram‐negative anaerobic bacteria, such as P. gingivalis . Additionally, permeability of the epithelial monolayer, in tissue culture inserts, increased in association with downregulation of E‐cadherin expression in response to exposure to P. gingivalis LPS, which suggested loss of E‐cadherin‐mediated formation of cellular junctions . These data are also consistent with our findings that showed decrease in resistance of stimulated oral epithelial monolayers to the passage of an electric current.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding was in agreement with the results from previous studies which indicated downregulation of E‐cadherin expression in the inflamed periodontal tissue in vivo and in vitro, and this was mostly attributed to gram‐negative anaerobic bacteria, such as P. gingivalis . Additionally, permeability of the epithelial monolayer, in tissue culture inserts, increased in association with downregulation of E‐cadherin expression in response to exposure to P. gingivalis LPS, which suggested loss of E‐cadherin‐mediated formation of cellular junctions . These data are also consistent with our findings that showed decrease in resistance of stimulated oral epithelial monolayers to the passage of an electric current.…”
Section: Discussionsupporting
confidence: 93%
“…This notion is supported by previous studies, which indicated that LPS is a potent EMT stimulus . In addition, treatment of oral gingival epithelium with E. coli LPS resulted in downregulation of E‐cadherin expression . For this reason , E. coli LPS was used as a positive control in our EMT studies.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Human gingival fibroblasts were serum-starved for 24 h then treated with 1 μg/mL E. coli LPS [ Escherichia coli LPS (O111:B4; Sigma-aldrich, St Louis, MO, USA)] (Herath et al, 2011 ) or 10 μg/mL P. gingivalis LPS (Invivogen, San Diego, CA, USA) (Abe-Yutori et al, 2017 ) at 2 or 20% O 2 for 6 h. Mouse gingival fibroblasts were serum-starved for 24 h then were treated with 1 μg/mL E. coli LPS at 2% O 2 for 1, 2, 4, and 24 h. Cells were collected and proteins were extracted in lysis buffer (Keygen Biotech Inc., Nanjing, China) and 20–30 μg of the total proteins were loaded and separated by using 10% SDS-PAGE. The following proteins were detected using antibodies, anti-human, -mouse NLRP3 (LifeSpan BioSciences, Seattle, WA, USA); anti-human, -mouse caspase-1 (Santa Cruz Biotechnology, Inc., Santa Cruz, CA, USA); anti-human IL-1β (Abcam; detect pro- and mature IL-1β) and anti-mouse IL-1β (Novus Biologicals, Inc., Littleton, CO, USA; detect pro- and mature IL-1β) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Rokumigan, which consists six different herbs, rehmanniae radix, dioscoreae rhizoma, corni fructus, hoelen, moutan cortex, and alismatis rhizoma, is one of the most common herbal formulas, and has been shown to inhibit IL-6 secretion in cultured gingival epithelial cells [94] . In addition to oriental medicine, Vitamin E and l -ascorbic acid 2-phosphate magnesium salt inhibit decreases in E-cadherin expression, the penetration of P. gingivalis -LPS and increases in TNF-α [95] ( Table 1 ).…”
Section: Regulation Of the Function On The Junctional Epitheliummentioning
confidence: 99%